2013
DOI: 10.1007/s00705-013-1946-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and phylogenetic analysis based on the B2L gene of orf virus from goats and sheep in China during 2009-2011

Abstract: As a zoonotic infectious disease, orf outbreaks have been reported in China in recent years. However, molecular epidemiology analysis has not been performed for Chinese orf virus (ORFV) strains. Here, we have identified 13 ORFVs from goats and sheep in China between 2009 and 2011. Thirty-four complete B2L sequences were used to construct a phylogenetic tree to elucidate the molecular epidemiology of ORFV in China. Nucleotide sequences of B2L genes of clinical samples and attenuated vaccine strains were aligned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…ELISA was found simples, sensitive and accurate for rapid diagnosis of Orf virus in human and animals in Egypt. Increasing the positive percent of Orf virus antibodies in the serum samples of human and animals may be due to cross reactivity with viruses belong family family Poxviridae this finding is in agreement with that obtained by [4,10].On the other hand this finding is disagreement with [42][43][44].They found that cross immunity between orthopoxvirus and ORF virus do not occur and the diseases caused by Orf virus species are identical in animals & humans.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…ELISA was found simples, sensitive and accurate for rapid diagnosis of Orf virus in human and animals in Egypt. Increasing the positive percent of Orf virus antibodies in the serum samples of human and animals may be due to cross reactivity with viruses belong family family Poxviridae this finding is in agreement with that obtained by [4,10].On the other hand this finding is disagreement with [42][43][44].They found that cross immunity between orthopoxvirus and ORF virus do not occur and the diseases caused by Orf virus species are identical in animals & humans.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, results that the isolated ORF virus from human is identical of Orf virus isolated from sheep and goat in Egypt as in Figures 4-6. PCR is a rapid, sensitive and specific tool in identifying several infectious diseases of veterinary importance as mention by [40][41][42][43]. Comparing different serological tests AGPT and IFAT with ELISA for detection of anti Orf virus antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Yang et al (2014) provided molecular evidence about the genetic variability of the major antigenic and virulence genes in the virus isolates from epidemic in Xinjiang (China). Zhang et al (2014) found three genotypes by molecular epidemiology analysis of orf virus from goats and sheep in China during 2009-2011, amino acid substitutions were dispersed among B2 polypeptides from wild and attenuated orf virus strains. The isolation and identification of orf virus from an outbreak in goats in the Rajasthan State of India .…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 96%
“…The Orf virus genome is the smallest of all other Poxviridae family members, is about 140 kbp linear double-stranded DNA with ~ 64% G+C content, closed hairpin loop at termini and genes located on both strands in bidirectional orientation (Zhang et al, 2014). At each pole 3 kbp DNA folds to form an inverted terminal repeat (ITR).The Orf virus genome contains 132 putative genes including 89 highly conserved genes and some variable genes (Delhon et al, 2004;Mercer et al, 2006).The central region (CORE) carries conserved genes whereas variable genes are located at the ends.…”
Section: Genome Organizationmentioning
confidence: 99%